Avaliação in vitro do efeito antimicrobiano da incorporação de nanopartículas de prata em cimento de ionômero de vidro - Sales, Ernanda Maria de Araújo (2016)
The fluoride release from glass CIV may be important for preventing caries around restorations, mainly due to their effects on the mineral phase of teeth and the remineralization process. Considering the lack of effect of fluorides on cariogenic bacteria, the incorporation of an antimicrobial agent in GIC could help to minimize the risk of recurrent caries. The incorporation of the silver nanoparticles (NAg) has been tested in various materials by having an antimicrobial effect with wide spectrum without leading to the development of bacterial resistance. The aim of this study was to evaluate the effect of NAg incorporation in GIC regarding the antimicrobial potential and inhibition of caries lesions adjacent to the restoration. NAg was incorporated into a commercial GIC that was compared with the unmodified GIC and with a compound commercially available silver alloy in composition. Enamel bovine blocks (8x8x4 mm), in which was held cavity preparation on the buccal surface (diameter: 4 mm and depth: 1.5 mm), were restored using the restorative material according to the groups: CIVC (Riva Self Cure®- control), CIVS (Riva Silver®- with silver alloy), CIVNAg0,5 (Riva Self Cure® + 0,5% NAg) and CIVNAg1 (Riva Self Cure® + 1% NAg). Three blocks of each group were subjected to biofilm formation of S. mutans for 5 days and microbiological experiment was done in triplicate. Antimicrobial effect was assessed by CFU counts (colony forming units) and dry weight analysis. The blocks subjected to microbiological model of caries induction were analyzed using the Knoop hardness test in longitudinal section of enamel, 50 µm and 100 µm from the restoration margin and to determine demineralization around restorations Delta S (ΔS) parameter was used. Data were analyzed using ANOVA (one factor) for data regarding the CFUs and dry weight as ANOVA (two factors) was used for Delta S data analysis, at a pre-determined significance level of 5 %. No statistically significant differences were observed in mean CFU (p = 0.644), dry weight (p = 0.569) and mineral loss of enamel (ΔS) to 50μm (p = 0.241) and 100μm (p = 0.777) between tested groups. The incorporation of Nag in concentrations tested in GIC showed no significant differences when compared to conventional GIC and GIC with silver alloy in antimicrobial activity and the effect on inhibition of caries lesions.